Poly(2,5-dihydroxy-1,4-benzoquinonyl sulfide) as an efficient cathode for high-performance aqueous zinc–organic batteries - Sun, Tao (2021)
Aqueous rechargeable zinc-ion batteries (ZIBs) have attracted considerable attention as a promising candidate for low-cost and high-safety electrochemical energy storage. However, the advancement of ZIBs is strongly hindered by the sluggish ionic diffusion and structural instability of inorganic metal oxide cathode materials during the Zn2+ insertion/extraction. To address these issues, a new organic host material, poly(2,5-dihydroxy-1,4-benzoquinonyl sulfide) (PDBS), has been designed and applied for zinc ion storage due to its elastic structural factors (tunable space and soft lattice). The aqueous Zn-organic batteries based on the PDBS cathode show outstanding cycling stability and rate capability. The coordination moieties (O and S) display the strong electron donor character during the discharging process and can act as the coordination arms to host Zn2+. Also, under the electrochemical environment, the malleable polymer structure of PDBS permits the rotation and bending of polymer chains to facilitate the insertion/extraction of Zn2+, manifesting the superiority and uniqueness of organic electrode materials in the polyvalent cation storage. Finally, quasi-solid-state batteries based on aqueous gel electrolyte demonstrate highly stable capacity under different bending conditions.